Characteristics of delirium and its association with sedation and in-hospital mortality in patients with COVID-19 on veno-venous extracorporeal membrane oxygenation - Sun, Philip Young-woo; Fanning, Jonathon; Peeler, Anna; Shou, Benjamin; Lindsley, John; Caturegli, Giorgio; Whitman, Glenn; Cha, Stephanie; Kim, Bo Soo; Cho, Sung-Min; , HERALD investigators (Frontiers in Medicine, 2023)
Background: Veno-venous extracorporeal membrane oxygenation (VV-ECMO) has been used in patients with COVID-19 acute respiratory distress syndrome (ARDS). We aim to assess the characteristics of delirium and describe its association with sedation and in-hospital mortality. Methods: We retrospectively reviewed adult patients on VV-ECMO for severe COVID-19 ARDS in the Johns Hopkins Hospital ECMO registry in 2020-2021. Delirium was assessed by the Confusion Assessment Method for the ICU (CAM-ICU) when patients scored -3 or above on Richmond Agitation-Sedation Scale (RASS). Primary outcomes were delirium prevalence and duration in the proportion of days on VV-ECMO. Results: Of 47 patients (median age=51), 6 were in a persistent coma, and 40 of the remaining 41 patients (98%) had ICU delirium. Delirium in the survivors (n=21) and non-survivors (n=26) was first detected at a similar time point (VV-ECMO day 9.5[5, 14] vs. 8.5[5, 21], p=0.56) with similar total delirium days on VV-ECMO (9.5[3.3, 16.8] vs. 9.0[4.3, 28.3] days, p=0.43). Non-survivors had numerically lower RASS scores on VV-ECMO days (-3.72[-4.42, -2.96] vs. -3.10[-3.91, -2.21], p=0.06) and significantly prolonged delirium-unassessable days on VV-ECMO with a RASS of -4/-5 (23.0[16.3, 38.3] vs. 17.0[6, 23], p=0.03), and total VV-ECMO days (44.5[20.5, 74.3] vs. 27.0[21, 38], p=0.04). The proportion of delirium-present days correlated with RASS (r=0.64, p<0.001), the proportions of days on VV-ECMO with a neuromuscular blocker (r=-0.59, p=0.001) and with delirium-unassessable exams (r=-0.69, p<0.001), but not with overall ECMO duration (r=0.01, p=0.96). Average daily dosage of delirium-related medications on ECMO days did not differ significantly. On an exploratory multivariable logistic regression, proportion of delirium days was not associated with mortality. Conclusions: Longer duration of delirium was associated with lighter sedation and shorter paralysis, but it did not discern in-hospital mortality. Future studies should evaluate analgosedation and paralytic strategies to optimize delirium, sedation level, and outcomes.